Defining the roles of inflammatory and anabolic cytokines in cartilage metabolism - Goldring, M B (2008)
In osteoarthritis (OA), adult articular chondrocytes undergo phenotypic modulation in response to alterations in the environment owing to mechanical injury and inflammation. These processes not only stimulate the production of enzymes that degrade the cartilage matrix but also inhibit repair. With the use of in vitro and in vivo models, new genes, not known previously to act in cartilage, have been identified and their roles in chondrocyte differentiation during development and in dysregulated chondrocyte function in OA have been examined. These new genes include growth arrest and DNA damage (GADD)45β and the epithelial-specific ETS (ESE)-1 transcription factor, induced by bone morpho-genetic protein (BMP)-2 and inflammatory cytokines, respectively. Both genes are induced by NF-κB, suppress COL2A1 and upregulate matrix meatalloproteinase-13 (MMP-13) expression. These genes have also been examined in mouse models of OA, in which discoidin domain receptor 2 is associated with MMP-13-mediated remodelling, in order to understand their roles in physiological cartilage homoeostasis and joint disease.